Is there any relationship between hypodontia and hyperdontia with taurodontism, microdontia and macrodontia? A retrospective study - KARGÜL, BETÜL (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Background: Hypodontia and hyperdontia may occur with other dental anomalies such as microdontia, taurodontism, talon cusp, macrodontia and germination. Aims: The aim of this study to evaluate the relationship between hypodontia and hyperdontia with taurodontism, macrodontia and microdontia. Subjects and Methods: In this retrospective study, 2,348 Turkish patients aged 7 to 12 years and treated between 01.01.2017 and 01.01.2018 in Bahcelievler Oral and Dental Health Hospital were evaluated. Data were collected and differences in the distribution of hypodontia and hyperdontia including other dental anomalies were analysed. Results: Of the total sample of 2,348 patients, 1,126 (48%) were girls, 1,222 (52%) were boys. Hypodontia was found in 177 children (93 girls (53%), 84 boys (47%)). The prevalence of hypodontia and hyperdontia were 7.5% and 0.9%. Taurodontism is the most common dental anomalies in hypodontia patients (39%) followed by microdontia (10%). Taurodontism was more prevalent in girls (42%) than in boys (36.5%). Microdontia was found in 10 patients and macrodontia was observed in 9 hypodontia patients. Hyperdontia was found in 21 children [8 girls (38%), 13 boys (62%)]. The most common supernumerary tooth found was mesiodens (85%) and it's more prevalent in boys (67%) than in girls (33%). Taurodontism is the most common dental anomaly (48%) following macrodontia (19%) and were found to be much more prevalent in boys (53%) (23%) than in girls (37.5%) (12.5%). Microdontia was found in only 1 boy (%7.7) in hyperdontia patients. Conclusion: Hypodontia and hyperdontia with taurodontism, microdontia, and macrodontia need much more complex treatment plan. All cases should be evaluated using interdisciplinary approach for appropriate treatment choice. This helps in longterm and effective treatment planning according to a child's individual requirements.
Keywords: Hyperdontia; hypodontia; macrodontia; microdontia; taurodontism; SUPERNUMERARY TEETH; DENTAL ANOMALIES; ORTHODONTIC PATIENTS; PREVALENCE; AGENESIS; CHILDREN